The Effect of Space Launches on Climate: A Legal and Policy Perspective - Rachita Agrawal (Advanced Space Law, 2024)
Energy production, transportation, and industrial operations, which have higher carbon footprints, are frequently the focus of climate change mitigation measures. It is important to keep in mind that the processes involved in outer space launch operations, such as manufacturing, shipping and infrastructure construction have environmental impacts as well. It is critical to take into account the possible effects of space launches on the Earth’s climate from a legal and regulatory perspective as the space industry is expanded rapidly. When rocket propellants burn, carbon dioxide (CO2) and harmful gases are released into the atmosphere, which contributes to greenhouse gas emissions from space launches. This research paper in Part II elaborates on human rights perspective to climate change. Part III investigates the influence of outer space activities on climate. In Part IV, the evaluation of the disproportionate effects of space launch emissions on marginalised and vulnerable populations is discussed, with an emphasis on the concepts of climate justice and equity. Part V conducts a study of national laws, international environmental treaties, space law and policy procedures asserting liability and determining compensation for potential climate damage resulting from space launch activities. Part VI proposes establishment of specific liability frameworks and policy considerations through international cooperation for space launch operations liable for any negative climate repercussions along with incentivizing sustainable propulsion technologies and supporting green infrastructure.